Asthma Control and Quality of Life of Asthma Patients At St General Hospital - Jatmiko susilo; Soleha Kurniawati (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2024)
Asthma is a chronic condition characterized by chronic airway inflammation that causes various respiratory symptoms that can severely impact a patient's daily life. Suboptimal control of asthma is associated with increased costs of care and treatment and decreased quality of life (QoL). This study aims to examine asthma control status and its relationship with the QoL of asthma patients at ST. General Hospital. This cross-sectional study involved 50 asthmatics aged 18-65 who attended ST. General Hospital. Two questionnaires were used: an asthma control test (ACT) and an adult asthma quality-of-life questionnaire (Mini-AQLQ). By using SPSS, the Spearman Rank test was employed to identify associations with a 95% confidence level. Of the 50 respondents studied, asthma status was categorized as partially controlled (50%), totally controlled (14%), and uncontrolled (36%). A significantly worse QoL was observed in respondents with uncontrolled asthma, whereas a good QoL (minimal or no impairment) was observed in partially controlled respondents (p = <0.001). There was a relationship between asthma control and the respondent's QoL (rho = 0.832). Appropriate treatment will increase asthma control and improve the QoL of patients treated at ST. General Hospital. Further research is needed to evaluate risk factors, psychological effects, and behavioral screening in poorly controlled asthma patients.